First sauropod bones from Italy offer new insights on the radiation of Titanosauria between Africa and Europe. (September 2016) - Dal Sasso, Cristiano; Pierangelini, Gustavo; Famiani, Federico; Cau, Andrea; Nicosia, Umberto
Abstract: Here we describe the first sauropod skeletal remains from the Italian peninsula that also represent the earliest record of titanosaurs in Southern Europe. Scattered bones, including an almost complete anterior caudal vertebra, were found in Cretaceous (Aptian–Albian) marine deposits, some 50 km East of Rome. The vertebra shows a bizarre and perhaps unique orientation of the zygapophyseal articular facets that renders their interpretation problematic. Phylogenetic retrofitting tests support the placement of the Italian titanosaur among basal lithostrotians. Palaeobiogeographic analysis based on the resulting phyletic relationships suggests an Afro-Eurasian route for the ancestors of the Italian titanosaur, a scenario compatible with the palaeogeographic evolution of the Italian microplates during the Cretaceous. Together with previously recorded titanosaurian-like ichnites from a Cenomanian locality in Latium, this new find suggests a quite long emersion for the Apenninic carbonate platform. We suggest that the Italian titanosaur was member of a population that crossed the western Tethys Sea through a "filtering bridge" composed of a chain of ephemeral islands and peninsulae, known as Periadriatic (Adria) carbonate platforms, that connected sporadically Africa and Europe since the Early Cretaceous. Graphical abstract: Highligths: Referable to Titanosauria gen. et sp. indet., earliest record in southern Europe. An Aptian–Albian basal titanosaurian with bizarre orientation of the zygapophyseal facets. Further evidence of Early Cretaceous sporadic connection between Africa and Europe.